Mental health challenges among Chinese international students during COVID-19: A systematic review and meta-analysis of depression and anxiety - Ying, Zhexi; Kondo, Akiko; Piao, Meihui (Journal of International Students, 2025)
The COVID-19 pandemic has disproportionately impacted the mental health of international students, particularly Chinese international students (CISs), who have faced heightened sociocultural stressors and racial discrimination. This review examines the prevalence of depression and anxiety among CISs and explores associated factors via the socioecological model. Nine electronic databases were searched from January 2020 to July 2023. A proportional meta-analysis using random effects models estimated the prevalence of depression in nine studies (n = 4,784 CISs) and that of anxiety in nine studies (n = 5,701 CISs). The pooled prevalence was 51% (95% CI: 36%–65%) for depression and 48% (95% CI: 35%–62%) for anxiety. A qualitative synthesis of associated factors included 23 studies involving 19,802 cases of CIS. Related factors included fear of infection, family conflicts, sociocultural dilemmas, and discrimination. Institutional support and Chinese cultural beliefs.